Meat-eating in India: Whose food, whose politics, and whose rights?. Issue 7 (October 2019) - Sathyamala, C
Transitioning towards a plant-based diet is considered both ethical and environmentally friendly from a Western perspective of high per capita consumption of flesh foods. However, in contemporary India, beef-eating has emerged as a political act of subversion in the context of its current ban by the Indian state which is transforming unapologetically into a theocracy under the aegis of Hindu fundamentalist groups. To understand the contemporary discourse on beef-eating, it is important to locate it in the discourse prevalent during the Independence movement, when there was an attempt to unify the Hindus to forge a nationalist identity, and to bring the 'outcaste' 'untouchables' – who were a sub-group acknowledged to consume beef – within the Hindu fold of 'caste purity'. Data from an ethnographic study of over fifteen months in a village in the Indian state of Tamil Nadu, demonstrate the place of flesh foods, including beef, in the everyday lives of people, and question the concept of a 'normative' Indian diet. The paper argues that contrary to the notion that vegetarianism is morally superior, in the context of Hinduism, where vegetarianism is a marker of upper caste identity, the food hierarchy is a function of the caste structure. Hence, the protests, particularly from the former 'untouchable' caste groups, reclaiming the right to eat transgressive foods as a marker of their identity, poses a serious challenge to upper caste hegemony. The violence which 'vegetarian' India has unleashed on such transgressions has laid open the structural violence embodied in the caste system and questions its claim to moral superiority.